KEKERAB ATAN BEBERAPA SPESIES IKAN PELANGI IRIAN (FAMILI MELANOTAENIIDAE) BERDASARKAN KARYOTIPE [The Closely Related of Some Rainbow Fishes (Melanotaeniidae) from Irian Based of Caryotipe] - Djamhuriyah S. Said; Hidayat Hidayat (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2005)
Family Melanotaenidae, known as Rainbow fishes consist of six genus and 53 species and distributed in Irian Jaya, Papua New Guinea, and Australia. Those fishes usually found in the river, swamp, or lakes which have clean water at about less than 1,500 in above sea level. The differentiation of the genus based on the shape of the jaw. Genus Melanotaenia has the most species (32 species). Some of them are endemic. The aim of the research is to explain the closely related of five species rainbow fishes: Glossolepis incisus/Gi, Melanotaenia boesemani/Mb, M. lacustris/Ml, M. maccullochi/Mm, and M. praecox/Mp based on the caryotype. The caryotype was examined on 2000. Diploid chromosome number of four species are 48 (2N=48) except M. lacustris lias (2N=46). Based on the Numeric Value of Chromosome Position(NVCP) the chromosome showed the shape were sub-metasentric, sub-telosentric, or telosentric. Analysis of the closely related of the five species studied based on NVC.P and relative chromosome length (RCL). Based on the NVCP showed Mp and Mm were in one group, than followed by Mb. Those three species (Mp, Mm, and Mb) made cne group with Gi. Melanotaenia lacustris has its own group. But based on the RCL analysis showed the different result. Analysis based on the shape of each number of chromosome and Gi as the outer (out group), Ml had the farthest relationship, so Ml has the farthest relationship with the four species.